2005
DOI: 10.1111/j.1600-0609.2004.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in adult hematopoietic cell transplant patients at least 5 yr after treatment: a comparison with healthy controls

Abstract: Patients who had survived their HCT for more than 5 yr did generally well in terms of global QOL. This is consistent with Kiss et al. (J Clin Oncol 2002;20:2334-2343), who found that chronic myeloid leukemia patients who were alive at least 10 yr after HCT report lower physical functioning in comparison to healthy controls. Problems in the areas of social functioning and financial difficulty can possibly be addressed by intensive rehabilitation processes integrating patients, family members and significant oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 28 publications
1
37
1
1
Order By: Relevance
“…2,4,18,23 However, even if HRQL analyses have not always been done with the same instruments, a high level of satisfaction with life quality and a progressive improvement over time has been frequently described. [1][2][3][5][6][7]23,24,26 It has been suggested that full recovery after HSCT may be a 3-to 5-year process. 3,7,24 Indeed, Kopp et al 26 observed in a investigation with the EORTC QLQ-C30 and FACT-BMT questionnaires that HRQL improves significantly within 1 year after HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,4,18,23 However, even if HRQL analyses have not always been done with the same instruments, a high level of satisfaction with life quality and a progressive improvement over time has been frequently described. [1][2][3][5][6][7]23,24,26 It has been suggested that full recovery after HSCT may be a 3-to 5-year process. 3,7,24 Indeed, Kopp et al 26 observed in a investigation with the EORTC QLQ-C30 and FACT-BMT questionnaires that HRQL improves significantly within 1 year after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][5][6][7]23,24,26 It has been suggested that full recovery after HSCT may be a 3-to 5-year process. 3,7,24 Indeed, Kopp et al 26 observed in a investigation with the EORTC QLQ-C30 and FACT-BMT questionnaires that HRQL improves significantly within 1 year after HSCT. In the present study, however, a significant correlation between HRQL and follow-up time was not observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dit is zeker van belang voor patiën-ten die lijden aan een chronische en ongeneeslijke ziekte waarbij behandelmethoden geen effect hebben op overlevingskansen, maar eerder worden toegepast om de symptomen terug te dringen en een terugval in het ziekteproces te voorkomen. Zo wees een eerdere studie uit dat patiënten die aan deze ziekte lijden de KvL aanzienlijk kunnen verbeteren door effectiever om te gaan met de symptomen van de ziekte en door de psycho-oncologische bijstand die ze daarbij ontvangen (Kopp et al, 2005).…”
Section: Inleidingunclassified